PRA-RANCANGAN INDUSTRI BAHAN PANGAN BERBAHAN DASAR UBI CILEMBU (IPOMEA BATATAS âCILEMBUâ) DENGAN SISTEM PENGERINGAN BERBASISKAN RADIASI INFRAMERAH : EVALUASI PROSES PENGERINGAN UBI JALAR CILEMBU (IPOMEA BATATAS âCILEMBUâ) DENGAN SISTEM BERBASISKAN RADIASI INFRAMERAH - Saputra, Hendrik
This study aims to evaluate the process of drying cilembu sweet potatoes on a simple infrared-based dryer designed by the author. In general, what will be done in this research is the determination of the most effective dryer specifications consisting of fan voltage (4V, 6V, 8V) and drying load (1 tray, 2 trays, 3 trays) with a load of about 150 grams per tray and modelling the drying process. Determination of specifications is based on system evaluation and drying results. The experimental design used in this study was one-variable-at-a-time (OVAT); the first variable tested was the fan voltage, then continued with the drying load. Based on this study, it was found that the drying process more faster with increasing fan voltage used but not significantly different. Furthermore, increasing the drying load will make the drying process longer, but the efficiency will be higher. Furthermore, it was found that the process of drying the yam can be predicted well using the Wang & Singh model. When evaluated from the system evaluation, it was obtained SEC value of 1,622 KWh / kg, efficiency of 23.22 %, activation energy of 103.79 W / kg and maximum drying rate of 0.263 % / minute, while when evaluated from the evaluation of drying results, obtained sweet potato flour with starch content of 74 % and ash content of 3.68 %. Based on all the results obtained in this study, it can be concluded that the most effective specification for this dryer is a fan voltage of 4V and a drying load of 0.5 kg.